2001
DOI: 10.1051/0004-6361:20010161
|View full text |Cite
|
Sign up to set email alerts
|

On the quiescence of the Hubble flow in the vicinity of the Local Group

Abstract: Abstract. Cepheid distances of local galaxies (< 7 Mpc) are used to study the very nearby velocity field, as pioneered by Sandage (1986) who also pointed out its remarkable properties: linearity and quietness. The new data show that the velocity dispersion in the distance range as seen from the barycentre of the Local Group 1 − 8 Mpc is as low as 38 km s −1 . The local rate of expansion coincides with the global Hubble constant. Down to 1.5 Mpc we cannot detect a deviation from the linear Hubble flow. This put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
60
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 13 publications
8
60
0
Order By: Relevance
“…The distances from the HST data also confirmed that the Hubble law works at surprisingly small scales as observed in independent studies (Sandage & Tammann 1975;Ekholm et al 2001;Karachentsev et al 2002). The Hubble diagram (velocity vs. distance) directly shows the local expansion rate H as given by these remarkable HST observations.…”
Section: Introductionsupporting
confidence: 84%
“…The distances from the HST data also confirmed that the Hubble law works at surprisingly small scales as observed in independent studies (Sandage & Tammann 1975;Ekholm et al 2001;Karachentsev et al 2002). The Hubble diagram (velocity vs. distance) directly shows the local expansion rate H as given by these remarkable HST observations.…”
Section: Introductionsupporting
confidence: 84%
“…Chernin 2001Ekholm et al 2001;Baryshev et al 2001;Byrd et al 2007;Niemi et al 2007;Teerikorpi et al 2008). Study of the Local Group enables one to learn not only the mass in the system, but simultaneusly, the local density of the dark energy itself.…”
Section: Discussionmentioning
confidence: 99%
“…He saw a mystery in the fact that the local expansion proceeds in a quite regular way. Moreover, the rate of expansion is similar, if not identical, to the global Hubble constant (Ekholm et al 2001;Thim et al 2003;Karachentsev 2005;Karachentsev et al 2002aKarachentsev et al , 2003bWhiting 2003). Originally, the Friedmann theory described the expansion of a smooth, uniform self-gravitating medium.…”
Section: The Virgocentric Flowmentioning
confidence: 98%